2018
DOI: 10.1021/acsami.7b19232
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Modified Glass Substrate for Analysis of Highly Volatile Chemical Warfare Agents by Paper Spray Mass Spectrometry

Abstract: Paper spray mass spectrometry has been shown to successfully analyze chemical warfare agent (CWA) simulants. However, due to the volatility differences between the simulants and real G-series (i.e., sarin, soman) CWAs, analysis from an untreated paper substrate proved difficult. To extend the analytical lifetime of these G-agents, metal-organic frameworks (MOFs) were successfully integrated onto the paper spray substrates to increase adsorption and desorption. In this study, several MOFs and nanoparticles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…As shown in Figure a, the characteristic peaks of MOF‐199 s (2θ = 6.7°, 9.5°, 11.7°, 13.3°, 14.6°, 16.6°, 17.3°, 18.9°, 25.8° and 29.2°), were evident. For the Ag NPs@MOF‐199 s (Figure b), those peaks of MOF‐199 s in Figure a were confirmed, supporting the conclusion that the immobilization of Ag NPs onto the porous MOF‐199 s does not change their crystal structures.…”
Section: Resultsmentioning
confidence: 83%
“…As shown in Figure a, the characteristic peaks of MOF‐199 s (2θ = 6.7°, 9.5°, 11.7°, 13.3°, 14.6°, 16.6°, 17.3°, 18.9°, 25.8° and 29.2°), were evident. For the Ag NPs@MOF‐199 s (Figure b), those peaks of MOF‐199 s in Figure a were confirmed, supporting the conclusion that the immobilization of Ag NPs onto the porous MOF‐199 s does not change their crystal structures.…”
Section: Resultsmentioning
confidence: 83%
“…While these two compounds have differing volatilities, previous experiments have indicated that GB and GF volatilize rapidly . Albeit with differing rates of volatility, the derivatization process allows for their direct capture on the PS substrate and retainment of the derivatized compound due to the lower volatility of the resulting complex.…”
Section: Resultsmentioning
confidence: 99%
“…More relevantly, explosives, herbicides from aqueous matrices, pesticides, and CWA simulants from biofluids have been shown to be effectively analyzed via paper spray mass spectrometry (PS‐MS). The spray substrate has been subjected to a multitude of modifications including the addition of metal–organic‐frameworks (MOFs), carbon nanotubes, silica, urea, silanes, molecularly imprinted polymer (MIPs), and wax printing, with each resulting in a specialized system catering to a specific matrix or target chemistry. For example, these innovative modifications have allowed for sub‐parts‐per‐trillion detections of therapeutic drugs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chosen material is suspended into an aqueous starch solution, sonicated, possibly heated to boiling (Wang et al, ), and then added to the Buchner funnel containing a filter paper. Coating materials of silica particles (Wang et al, ), metal organic frameworks (MOFs) (Wang et al, ; Dhummakupt et al, ), metal oxides (Zheng et al, ,b), and polystyrene (Wang et al, ; Li et al, ) were studied. Silica particles were observed to fill pores and rest on the paper surface, adhered by the starch (Zheng et al, ).…”
Section: Direct Analysis Of Molecules In Native Statementioning
confidence: 99%